Questions about language what everyone should know about language in the 21st century - Bauer, Laurie, d 1949; Calude, Andreea S. (Taylor and Francis, 2020)
"Questions about Language sets out to answer, in a readable yet insightful format, a series of vital questions about language, some of which language specialists are regularly asked, and some of which are so surprising that only the specialists think about them. With an introduction by the editors, in this handy guide, sixteen experts in the field answer some challenging questions about language from, What makes a language a language? to Do people swear because they don't know enough words? Illustrating the complexity of human language, and the way in which we use it, the twelve chapters each end with a section on further reading for anyone interested in following up on the topic. Covering core questions about language, this is essential reading for both students new to language and linguistics and the interested general reader"--